Nutrition has a pervasive impact on cardiac microRNA expression in isogenic mice. Issue 7 (2nd July 2016) - Wing-Lun, Edwina; Eaton, Sally A.; Hur, Suzy S. J.; Aiken, Alastair; Young, Paul E.; Buckland, Michael E.; Li, Cheryl C. Y.; Cropley, Jennifer E.; Suter, Catherine M.
ABSTRACT: The complex interaction between obesity, Western-style diets, and cardiovascular disease is of increasing interest, with a growing number of children being born to obese parents with poor lifestyle choices. These offspring have themselves an increased susceptibility to obesity and subsequent cardiovascular disease in adult life, which may be 'programmed' by their intrauterine environment. Cardiac microRNAs (miRNAs) are affected by multiple disease states, and have also been shown to be capable of exerting a hormone-like control on whole body metabolism. Here we sought to determine the effect of prenatal exposure to maternal obesity and/or postnatal exposure to a Western diet on miRNA expression in the heart. Unbiased small RNA sequencing was carried out on cardiac tissue from young adult mice born to lean or obese mothers; offspring were weaned onto either a low-fat control diet or a high-fat Western-style diet. We found 8 cardiac miRNAs that were significantly altered in response to maternal obesity, but only when the offspring were challenged postnatally with the Western diet. In contrast, postnatal exposure to the diet alone induced significant changes to the expression of a much larger number of miRNAs (33 in offspring of lean and 46 in offspring of obese). Many of the affected miRNAs have previously been implicated in various cardiac pathologies. The pervasive cardiac miRNA changes induced by a Western diet suggest that an individual's lifestyle choices outweigh the impact of any programming effects by maternal obesity on miRNA-related cardiac health.